MiR-27a-3p protects against NaAsO2-induced neuronal apoptosis in HT22 cells - Qiyao Zhang; Siqi Zhao; Teng Ma; Yujie Wang; Shiqing Xu; Suhua Wang; Xiaohui Wang; Li Wang (Scientific Reports)
Abstract Environmental arsenic exposure is closely related to nerve damage. Recent research suggests miR-27a-3p is involved in the development of certain neurodegenerative and neuropsychiatric diseases. Nonetheless, the precise impact of miR-27a-3p on neuron functioning in the hippocampus remains unclear. In this investigation, models were established using NaAsO2-treated mice and cells to investigate this aspect. Male C57BL/6J mice were given drinking water containing sodium arsenite (0, 0.5, 5, or 50 ppm) for 48 weeks. The results showed that sodium arsenite induced apoptosis in mouse neurons. After 6 μmol/L sodium arsenite treatment in HT22 cells, miR-27a-3p expression level was decreased, FTO, DRP1 and p-DRP1 (Ser616), neuronal apoptosis and pro-apoptotic proteins (Bax and cleaved asparaginase 3) were increased, and anti-apoptosis proteins Bcl-2 and MMP were decreased, which indicated that sodium arsenite could activate FTO/DRP1 pathway. Furthermore the process could be reversed by miR-27a-3p mimics. This study demonstrates that miR-27a-3p alleviates sodium arsenite-induced mitochondrial dysfunction and apoptosis in HT22 cells by inhibiting the FTO/DRP1 pathway. This study provides a scientific basis for finding early biomarkers for the control of arsenic-induced neurotoxicity and discovering new prevention and control measures.